Technical evaluation and usability of a quantitative G6PD POC test in cord blood: a mixed-methods study in a low-resource setting - François Nosten; Rose McGready; Mary Ellen Gilder; Borimas Hanboonkunupakarn; Verena Ilona Carrara; Germana Bancone; Elsie Win; Gornpan Gornsawun; Laypaw Archasuksan; Nan San Wai; Sylverine Win; Penporn Penpitchaporn; et al. (BMJ Open)
Objectives New point-of-care (POC) quantitative G6PD testing devices developed to provide safe radical cure for Plasmodium vivax malaria may be used to diagnose G6PD deficiency in newborns at risk of severe neonatal hyperbilirubinaemia, improving clinical care, and preventing related morbidity and mortality.Methods We conducted a mixed-methods study analysing technical performance and usability of the ‘STANDARD G6PD’ Biosensor when used by trained midwives on cord blood samples at two rural clinics on the Thailand–Myanmar border.Results In 307 cord blood samples, the Biosensor had a sensitivity of 1.000 (95% CI: 0.859 to 1.000) and a specificity of 0.993 (95% CI: 0.971 to 0.999) as compared with gold-standard spectrophotometry to diagnose G6PD-deficient newborns using a receiver operating characteristic (ROC) analysis-derived threshold of ≤4.8 IU/gHb. The Biosensor had a sensitivity of 0.727 (95% CI: 0.498 to 0.893) and specificity of 0.933 (95% CI: 0.876 to 0.969) for 30%–70% activity range in girls using ROC analysis-derived range of 4.9–9.9 IU/gHb. These thresholds allowed identification of all G6PD-deficient neonates and 80% of female neonates with intermediate phenotypes.Need of phototherapy treatment for neonatal hyperbilirubinaemia was higher in neonates with deficient and intermediate phenotypes as diagnosed by either reference spectrophotometry or Biosensor.Focus group discussions found high levels of learnability, willingness, satisfaction and suitability for the Biosensor in this setting. The staff valued the capacity of the Biosensor to identify newborns with G6PD deficiency early (‘We can know that early, we can counsel the parents about the chances of their children getting jaundice’) and at the POC, including in more rural settings (‘Because we can know the right result of the G6PD deficiency in a short time, especially for the clinic which does not have a lab’).Conclusions The Biosensor is a suitable tool in this resource-constrained setting to identify newborns with abnormal G6PD phenotypes at increased risk of neonatal hyperbilirubinaemia.